Implementation of a Steam-Based Module Integrating Mathematics Geometry to Cultivate Vocational Values - Diniah Pratama Putri; Nur Qudus; Ade Novi Nurul Ihsani (Journal of Vocational and Career Education, 2024)
The quality of education is highly influenced by the use of appropriate methods and media, particularly for subjects requiring high analytical skills, such as problematic facial skin care at SMKN 1 Salatiga. This study aims to develop and test the effectiveness of Moodle-based e-learning media in enhancing the analytical abilities of students. The research employed a quasi-experimental design with a control group, involving pre-tests and post-tests. Data were collected through tests, observations, and student response questionnaires, analyzed using descriptive and inferential statistical tests. The results indicated a significant improvement in learning outcomes after using Moodle e-learning media compared to conventional methods, with a statistically higher post-test average score (Sig. < 0.05). Student responses to this media were overwhelmingly positive, with an average satisfaction rate of 85.44 percent, particularly regarding accessibility and visual appeal. This study concludes that Moodle-based e-learning effectively enhances analytical skills, supports active learning, and provides an interactive and flexible learning experience. This research contributes to the development of digital media applicable to vocational education, preparing students to meet technology-driven workforce challenges.